2021
DOI: 10.1186/s13567-020-00888-5
|View full text |Cite
|
Sign up to set email alerts
|

3D skin models in domestic animals

Abstract: The skin is a passive and active barrier which protects the body from the environment. Its health is essential for the accomplishment of this role. Since several decades, the skin has aroused a strong interest in various fields (for e.g. cell biology, medicine, toxicology, cosmetology, and pharmacology). In contrast to other organs, 3D models were mostly and directly elaborated in humans due to its architectural simplicity and easy accessibility. The development of these models benefited from the societal pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 146 publications
(154 reference statements)
0
13
0
Order By: Relevance
“…These 3D models allow unmixing co-culturing of layers of different cells (fibroblasts, keratinocytes, melanocytes etc.) to proliferate and interact vertically and horizontally all cell components within an extracellular matrix developing highly comprised artificial tissue 36 . Therefore, human full thickness skin equivalents has multiple use and benefits in examining not only how newly developed drugs/cosmetics with epidermal and dermal cells, but epidermal gene expression and understanding the roles these two layers in disease modelling and wound healing.…”
Section: Culturing Fse On Two Photon Printed 3d Scaffolds With Custom...mentioning
confidence: 99%
“…These 3D models allow unmixing co-culturing of layers of different cells (fibroblasts, keratinocytes, melanocytes etc.) to proliferate and interact vertically and horizontally all cell components within an extracellular matrix developing highly comprised artificial tissue 36 . Therefore, human full thickness skin equivalents has multiple use and benefits in examining not only how newly developed drugs/cosmetics with epidermal and dermal cells, but epidermal gene expression and understanding the roles these two layers in disease modelling and wound healing.…”
Section: Culturing Fse On Two Photon Printed 3d Scaffolds With Custom...mentioning
confidence: 99%
“…Studies to develop 3D skin models in animals originally started for use in the pharmaceutical and cosmetic industries ( 116 ). Initially, pig skin was considered a good model to test drugs of topical formulation ( 117 ).…”
Section: Development Of Farm and Companion Animal Organoid Models: Hi...mentioning
confidence: 99%
“…Initially, pig skin was considered a good model to test drugs of topical formulation ( 117 ). At present, availability of animal skin models are very limited due to the development of human 3D skin models and most of them are developed for use in veterinary medicine or comparative biology research ( 116 ). Nonetheless, investigation of animal skin models possesses some values in studies on comparative biology and skin diseases such as bacterial and atopic dermatitis in dogs, which hold similar clinical course and presentation to those in humans ( 118 ).…”
Section: Development Of Farm and Companion Animal Organoid Models: Hi...mentioning
confidence: 99%
“…With over thirty years of research in this area there are numerous datasets available for skin absorption modelling studies, ranging in many parameters including the number of compounds considered, the source and thickness of skin used, experimental temperature, pH and vehicle composition 10 13 . Prior to this study, the vast majority of data used in creating permeation models is based on animal skin studies which are renowned for being poor mimics for human skin, a phenomenon known as the inter-species translational gap 14 , 15 . One study in particular found that only four of the thirty three QSPRs available at the time of publication were deemed ‘acceptable’ according to their stated four criteria with only one of these providing ‘reasonable’ predictions 16 .…”
Section: Introductionmentioning
confidence: 99%